2019
DOI: 10.3390/app9163254
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Scanning Temperature on the Classification of Whisky Samples Analysed by UV-VIS Spectroscopy

Abstract: The definition of the optimal temperature and its effects (either increasing or variations) during analysis of alcoholic beverages are of importance to develop protocols based in spectroscopy. Although several reports have been published on the use of spectroscopy combined with chemometrics to classify and authenticate alcoholic beverages (e.g., wine, tequila, whisky), few reports deal with issues related with the spectra collection (e.g., temperature, path length) and its effect on the classification performa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 29 publications
1
10
0
Order By: Relevance
“…The UV‐Visible spectroscopic analysis of the Scotch Whisky samples showed absorbance in similar regions to the UV spectra of other distilled alcoholic beverages, with the bulk of absorbance occurring between 200‐300 nm. This result is consistent with spectroscopic measurements of Scotch Whisky in the UV‐Visible range ( 48, 49, 77 ) . These peaks correspond to congeners produced during fermentation and maturation such as vanillin.…”
Section: Resultssupporting
confidence: 90%
See 3 more Smart Citations
“…The UV‐Visible spectroscopic analysis of the Scotch Whisky samples showed absorbance in similar regions to the UV spectra of other distilled alcoholic beverages, with the bulk of absorbance occurring between 200‐300 nm. This result is consistent with spectroscopic measurements of Scotch Whisky in the UV‐Visible range ( 48, 49, 77 ) . These peaks correspond to congeners produced during fermentation and maturation such as vanillin.…”
Section: Resultssupporting
confidence: 90%
“…Spectrophotometry results were obtained using a double beam Specord 210 Plus spectrophotometer (Analytik Jena AG, Jena, Germany). The variable bandwidth of the instrument was set to measure between 200 and 900 nm in agreement with previous studies ( 48, 49 ) . Samples were diluted by a factor of 10 using Milli‐Q water and compared with reference samples of Milli‐Q water.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, Joshi et al [71], also reported the successful application of UV-Vis combined with chemometrics to classify whisky samples from several geographical regions. The authors reported that PLS-DA models correctly classified 100% of the whisky samples belonging to the USA and Canada and 98% of those belonging to Scotland and Ireland respectively.…”
Section: Recent Innovations In Adulterant Analysismentioning
confidence: 93%